Southern as a second language - Patton, Lisa (Thomas Dunne Books/St. Martin's, 2013)
Leelee Satterfield's efforts to run a new restaurant with Peter are challenged by her unpredictable friends, a male dog named Roberta, and the return of Leelee's notorious ex-husband.